(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Since their birth the human beings are fiercely fighting to survive and to achieve prosperity. During their entire life, the purpose is to obtain a higher comfort, which they perceive as a way towards perfect happiness. Focusing on this goal, men often overcome the voice of their moral consciousness and make all the efforts to reach their targets, even by sacrificing their human relations or their own character. Based on these human nature tendencies, Christianity comes to completely reverse the values: instead of stubbornness it suggests self-surrender and replaces the anxious control of life with a constant and deep faith in God.